Salicornia L. (Amaranthaceae) in South Africa and Namibia: rapid spread and ecological diversification of cryptic species - Slenzka, A.; Mucina, Ladislav; Kadereit, G. (Wiley-Blackwell Publishing Ltd., 2013)
In Salicornia, morphology does not provide reliable diagnostic characters supporting the true extent of evolutionary divergence in the genus, and species concepts have been challenged by molecular analyses. Here, we report the results of an analysis of 91 accessions of the S.?meyeriana complex from South Africa and Namibia using the measurements of 38 morphological traits and external transcribed spacer (ETS) sequence data. Morphological data were analysed using discriminant analysis, principal coordinate analysis and nonmetric multidimensional scaling. Phylogenetic divergence was compared with the geographical and ecological diversity of the sampled populations. Tree topology corresponds to geography and ecology, but not to morphology. Most clades have distinct distribution areas and ecological profiles related to tidal, supratidal or inland saline habitats. Salicornia probably diversified in habitats that have experienced regular fragmentation by marine transgression/regression cycles during the Pleistocene. We suggest that this radiation produced young, but genetically, geographically and ecologically well-defined lineages. The lack of morphological signal reveals the existence of cryptic species in Salicornia and demonstrates the necessity of using molecular data to define taxa in this genus. We propose the recognition of two subspecies in the S.?meyeriana complex: S.?meyeriana subsp. meyeriana and S.?meyeriana subsp. knysnaensis. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 172, 175–186.